Bringing Books to Blooms: Service Learning Initiatives Enrich Rural Schools with Outdoor Reading Nooks - Daud, Ramlah; Hasri, Khairey Hazriq Bin; Osman, Aidil Idham Bin; Yusof, Mohamad Izzan Yusri Bin; Jilis, Aiman Nadzwa Bin; Nasip, Mohd Haizal Arash Bin Hazman (IJOCSE: Indonesian Journal of Community Services, 2024)
The SULAM (Service learning Malaysia-University for Society)project aims to bridge educational gaps in rural areas while providing University Malaysia Sabah (UMS) students with practical, community-focused learning experiences. As part of a Social Inequality course, 156 students collaborated to construct an outdoor reading nook for Sekolah Kebangsaan Kokol in Sabah. Despite challenges related to the remote location and limited resources, the students successfully created a vibrant learning environment, including a playground and fish pond. Organized into specialized teams, they undertook task such as construction, fundraising, and community engagement. This project not only enhanced the educational infrastructure of SK Kokol but also demonstrated the value of service learning in addressing social disparities and fostering civic responsibility among students. The initiative underscores the importance of integrating practical, community-oriented activities into academic curricula to promote social equity and develop socially conscious graduates.